THE EFFECT OF FARMER BEHAVIOR ON THE PRODUCTIVITY OF CRYSTAL GUAVA ON FARMERS' GROUP IN SEMARANG CITY - Refida Nugrahayu Widyastuti; Sriroso Satmoko; Tutik Dalmiyatun (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
The productivity of crystal guava is influenced by farmers' behavior (knowledge, attitudes, and skills). The research objectives were to 1) analyze the behavior of crystal guava farmers, 2) analyze the productivity level of crystal guava 3) analyze the effect of farmer behavior on the productivity of crystal guava in the Crystal Guava Farmers Group Semarang City. The research was carried out from December 10, 2018, to January 27, 2019. The study was carried out in 3 locations: Cepoko Village, Gunungpati District, Bubakan Village, Mijen District, and Wates Village, Ngaliyan District. The method used is the census method. Data was collected through interviews using questionnaires and field observations. Data analysis was carried out descriptively and using multiple linear regression analysis. The results showed that 1) the level of knowledge of farmers was in the high category, the level of attitude was in the medium class, and the skill level was in the medium category, 2) the productivity level of crystal guava is moderate with indicators of high production yield, medium capital, and low labor, 3) the behavior of farmers affects the productivity of crystal guava simultaneously. Attitude does not affect productivity partially.